The Sporting Lifestyle of Armenian Schoolchildren - Asatryan, Vahan (Journal of Sociology: Bulletin of Yerevan University, 2012)
As a result of sociological survey of the teachers of physical training a conclusion has been drawn about the importance of extracurricular sectorial trainings on different kinds of sports. A special vital role of basketball in the system of the classes of physical culture has been defined. It has been acknowledged to restore the so-called "section sports" classes at general public schools and basketball classes in particular.